2018
DOI: 10.1016/j.steroids.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers of glucocorticoid response and safety in anti-neutrophil cytoplasmic antibody-associated vasculitis and juvenile dermatomyositis

Abstract: Glucocorticoids are standard of care for many chronic inflammatory conditions, including juvenile dermatomyositis (JDM) and anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). We sought to define pharmacodynamic biomarkers of therapeutic efficacy and safety concerns of glucocorticoid treatment for these two disorders. Previous proteomic profiling of patients with Duchenne muscular dystrophy (DMD) and inflammatory bowel disease (IBD) treated with glucocorticoids identified candidate biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…This antiinflammatory mechanism of action has been monitored in human trials and studies through reductions of blood biomarkers (CD23, insulin like growth factor binding protein 2 , interleukin-22-binding protein [IL22BP], MMP12, macrophage-derived chemokine/C-C motif chemokine 22 [MDC/CCL22], and lymphotoxin α1/β2). 15,16 A first-in-human phase 1 study in 86 healthy male adults showed that the pharmacokinetics (PK) of vamorolone was linear within a broad dose range (0.1-20 mg/kg/day), and vamorolone was safe and well tolerated at all doses, as indicated by biomarker measurements. Serum biomarkers reflecting typical side effects associated with traditional glucocorticoids such as increased fasting insulin and glucose levels (insulin resistance) and decreased osteocalcin (bone formation) showed no significant change in any vamorolone dose group compared with placebo.…”
Section: Vamorolonementioning
confidence: 99%
See 1 more Smart Citation
“…This antiinflammatory mechanism of action has been monitored in human trials and studies through reductions of blood biomarkers (CD23, insulin like growth factor binding protein 2 , interleukin-22-binding protein [IL22BP], MMP12, macrophage-derived chemokine/C-C motif chemokine 22 [MDC/CCL22], and lymphotoxin α1/β2). 15,16 A first-in-human phase 1 study in 86 healthy male adults showed that the pharmacokinetics (PK) of vamorolone was linear within a broad dose range (0.1-20 mg/kg/day), and vamorolone was safe and well tolerated at all doses, as indicated by biomarker measurements. Serum biomarkers reflecting typical side effects associated with traditional glucocorticoids such as increased fasting insulin and glucose levels (insulin resistance) and decreased osteocalcin (bone formation) showed no significant change in any vamorolone dose group compared with placebo.…”
Section: Vamorolonementioning
confidence: 99%
“…The assessed exploratory PD biomarkers are proinflammatory mediators related to NF-κB pathways that were previously shown to be responsive to GC treatment in children with DMD, inflammatory bowel disease, juvenile dermatomyositis and ANCA-associated vasculitis. 15,20 We hypothesized that defining exposure-response relationships of these serum proteins at 2 weeks of treatment with vamorolone would be an objective means of evaluating drug mechanism of action and potentially predicting later clinical improvements at 6 months of treatment.…”
Section: Data Sourcesmentioning
confidence: 99%
“…An alternative approach that is increasingly used is molecular biomarkers (proteins, RNA) as a PD outcome measure. As an example, a set of serum proteins involved in inflammation and responsive to corticosteroids was defined in 3 pediatric disease states (Duchenne muscular dystrophy, pediatric inflammatory bowel disease, juvenile dermatomyositis) and 1 disease in adults (Antineutrophil antibody‐associated vasculitis) . These were then used to test the anti‐inflammatory effects of a new drug, vamorolone, in Duchenne muscular dystrophy .…”
Section: Use Of Biomarkers As Pd End Pointsmentioning
confidence: 99%
“…As an example, a set of serum proteins involved in inflammation and responsive to corticosteroids was defined in 3 pediatric disease states (Duchenne muscular dystrophy, pediatric inflammatory bowel disease, juvenile dermatomyositis) and 1 disease in adults (Antineutrophil antibody-associated vasculitis). [33][34][35] These were then used to test the anti-inflammatory effects of a new drug, vamorolone, in Duchenne muscular dystrophy. 36 Initial dose-ranging pediatric trials in Duchenne muscular dystrophy studied a 24-fold dose range (0.25-6.0 mg/kg/day), in which the serum pharmacodynamics biomarkers helped to establish the likely efficacious doses with only a 2-week exposure study.…”
Section: Use Of Biomarkers As Pd End Pointsmentioning
confidence: 99%
“…Vamorolone is a first-in-class alternative to glucocorticoids (GCs), under development for children with Duchenne muscular dystrophy (DMD); preliminary findings demonstrate improved safety compared with GCs 1,2 . We sought to define NFkB-regulated, GC-responsive serum biomarkers for use in a proof-of-concept pilot trial of vamorolone in UC, focusing on TFF3 (produced by intestinal epithelia, GC-responsive in UC), and CCL22 (produced by macrophages, GC-responsive in UC and other inflammatory diseases) 3,4 . Methods Sera from 10 children with IBD (7 UC, 3 CD) were tested pre and post prednisone/prednisolone (1 mg/kg/day, max 40 mg, 1-4 weeks); 210 proteins responsive to GCs in UC 3 were analyzed using SOMAscan.…”
mentioning
confidence: 99%